The Impact of the Meningococcal Serogroup C Conjugate Vaccine in Canada Between 2002 and 2012. (28th July 2014) - Sadarangani, Manish; Scheifele, David W.; Halperin, Scott A.; Vaudry, Wendy; Le Saux, Nicole; Tsang, Raymond; Bettinger, Julie A.; Bridger, N.; Morris, R.; Halperin, S.; Top, K.; Déry, P.; et al.
Abstract : The meningococcal serogroup C conjugate vaccine has significantly reduced serogroup C meningococcal disease in Canada, despite different immunization schedules used in different provinces. Direct and indirect protection was achieved with the largest reduction in the 15–24 year age group. Abstract: Background. Before 2001, the incidence of invasive meningococcal disease (IMD) in Canada was 1.0 per 100 000 per year, with 40% of cases caused by serogroup C organisms. During 2001–2005 all provinces introduced the meningococcal serogroup C conjugate vaccine (MCCV) into their routine infant immunization schedule. Methods. Active, prospective, population-based surveillance of IMD in children and adults was conducted by the Canadian Immunization Monitoring Program, ACTive (IMPACT) during 2002–2012. Inclusion criteria were admission to hospital and identification of Neisseria meningitidis from a sterile site. Incidence was estimated using population census data from Statistics Canada. Results. Prior to MCCV introduction, serogroup C disease incidence was 0.07–0.25 per 100 000 per year depending on the province. Following vaccine introduction, serogroup C disease decreased to <0.05 per 100 000 per year, with a reduction of 14% per year ( P = .0014). A decrease occurred in all provinces, despite differing schedules being implemented. The largest decrease of 83% (from 0.27 to 0.05 per 100 000 per year) occurred in the 15–24 year age group ( P = .0100) who were not vaccinated in all provinces. There was no impact on the incidence of nonserogroup C disease over the same period ( P = .9811). Conclusions. MCCV dramatically reduced the incidence of serogroup C IMD in Canada through both direct and indirect effects. The observation that disease incidence decreased with different schedules suggests that the doses at 12 months (common to all provinces) and adolescence (7 of 8 provinces studied) were critical in achieving disease control.